Swimming as an occupation for children with autism spectrum disorder: parent and swimming teacher perceptions and experiences - Carter, Bronwyn Claire (My University, 2021)
Background: Swimming as an occupation for children with ASD is an unexplored field of research in the South African context. Aims: The purpose of this study was to explore the experiences of swimming teachers and parents of children with ASD in the context of swimming lessons. Methods: Semi-structured in-depth interviews were utilized and a qualitative, descriptive-phenomenological design. Colaizzi seven-step method for data analysis was utilized. Results: Findings showed that parent’s often sought swimming lesson’s as they perceived their children to be at an increased risk of drowning due to the characteristic features of their diagnosis. Parent’s experienced swimming as a valuable and meaningful occupation for their children with ASD and experienced a number of additional benefits, such as experiences of belonging and pride, which they had not first anticipated. However, they experienced a variety of barriers to accessing this service. Swimming teacher’s also derived meaning and fulfilment from providing lessons. Although their perceptions and knowledge of ASD changed and grew as they interacted more with the children and their families, they expressed a definite need for greater support and training. Conclusion: Swimming is a meaningful and valuable occupation for children with ASD and their families, but swimming teachers in South Africa are not always equipped to provide this service. Occupational therapist could play a number of different roles in supporting participation for all stakeholders
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Occupational Therapy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2021